Scurvy in a boy with thalassemia major. - Phiske, M.M.; Rathod, P.R.; Dhurat, R.S.; Jerajani, H.R. (European Journal of Pediatric Dermatology, 2012)
Scurvy is a rare disease of unknown incidence characterized by alterations in bone, skin and mucous membrane, resulting from a deficiency of vitamin C. Dramatic response to vitamin C therapy can be used to confirm the diagnosis in the absence of laboratory tests. A rare case of scurvy in case of thalassemia major is reported.